PENGEMBANGAN MEDIA VIDEO TUTORIAL PADA KEGIATAN PRAKTIKUM BIOLOGI UNTUK SISWA SMA - Sri Zura Aziza; Mariani Natalina. L; Zulfarina Zulfarina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstarct: This study aims to develop video tutorials for biology practicum activities for high school students, analyze the feasibility of video tutorials for practicum activities, analyze the use of video tutorials for biology practicum activities for high school students. This type of research is development research using the ADDIE model. This research is carried out until stage 3, which is the development stage. Instruments used for data collection are validation sheets, response questionnaire sheets. The trial was conducted on students of class XI SMAN 1 Pekanbaru. The results showed that the video tutorial media for biology practicum activities for high school students was very feasible with an average value of 93.59. The video usability analysis was obtained from the results of the first trial with an average value of 93.75 and the second trial with an average value of 91.01 with a very good category. This shows that the video tutorial developed is very feasible to be used as a learning resource.Key Words: Media, Video Tutorials, Practical Activities.